Peptidergic activation of transcription and secretion in chromaffin cells. Cis and trans signaling determinants of pituitary adenylyl cyclase-activating polypeptide (PACAP). - Taupenot, L (1998)
Pituitary adenylyl cyclase-activating polypeptide (PACAP) is a potent endogenous secretagogue for chromaffin cells. Chromogranin A is the major soluble core component in secretory vesicles. Since chromogranin A is secreted along with catecholamines, we asked whether PACAP regulates expression of the chromogranin A gene in PC12 rat chromaffin cells, so as to resynthesize the just-secreted protein, and whether such biosynthetic regulation is coupled mechanistically to catecholamine secretion. PACAP activated the endogenous chromogranin A gene by four- to fivefold. Proportional results (seven- to eightfold activation) were obtained with a transfected 1,200-bp mouse chromogranin A promoter/luciferase reporter construct. A series of chromogranin A promoter 5' deletion mutant/luciferase reporter constructs narrowed down the PACAP response element to a proximal region containing the cAMP response element (CRE box), at (-71 bp)5'-TGACGTAA-3'(-64 bp). Site-directed point mutations of the CRE site suppressed PACAP-induced trans-activation of the promoter. Thus, the proximal CRE box is entirely necessary for the chromogranin A promoter response to PACAP. Transfer of the CRE box to a neutral, heterologous promoter also conferred activation by PACAP, suggesting that the CRE domain is also sufficient to mediate the transcriptional response to PACAP. Expression of a dominant-negative mutant (KCREB) of the CRE-binding factor CREB markedly diminished trans-activation of the chromogranin A promoter by PACAP. Cotransfection of expression plasmids encoding the protein kinase A inhibitor, or an inactive protein kinase A (PKA) catalytic beta subunit, inhibited both forskolin and PACAP activation of chromogranin A transcription, revealing that PACAP-induced trans-activation is highly dependent on PKA. By contrast, inhibition of protein kinase C (by chronic exposure to phorbol ester) had no effect on transcriptional activation by PACAP. The potent PACAP/vasoactive intestinal peptide (VIP) type I receptor antagonist PACAP6-38 impaired both chromogranin A transcription or catecholamine secretion triggered by PACAP38, while the PACAP/VIP type II receptor antagonist (p-Chloro-D-Phe6, Leu17)-VIP had little or no ability to antagonize the PACAP38 effect. The agonist VIP was approximately 100- to 1,000-fold less potent than PACAP in stimulating either secretion or transcription. Thus, PACAP-evoked chromogranin A transcription and catecholamine secretion are likely mediated by the PACAP/VIP type I receptor isoform. Although the calcium channel antagonists Zn2+ (100 microM), nifedipine (10 microM), or ruthenium red (10 microM), or the cytosolic calcium chelator BAPTA-AM (50 microM) each strongly impaired PACAP-induced secretion, transcriptional activation of chromogranin A remained unaltered. Therefore, we propose that PACAP signals to chromogranin A transcription through the CRE in cis, and through PKA and CREB in trans. By contrast, a pathway involving cytosolic calcium entry through L-type voltage-dependent channels is required for PACAP to evoke catecholamine secretion.